Membongkar realitas kerja paksa di balik megahnya jalan anyer-panarukan dalam bidang ekonomi - Ulum, Ilsa Fikrotul (Maliki Interdisciplinary Journal, 2025)
Under the administration of Governor General Herman Willem Daendels, the Anyer-Panarukan road, which spanned 1,000 kilometers on Java Island, was one of the Dutch colonial infrastructure megaprojects in the early 1800s. The road's prestige as a strategic trade and transportation route hides the facts about forced labor, exploitation of indigenous labor, and its impact on local economic structures. Through an economic history approach, this study analyzes how the forced labor system and forced indentured servitude affected agribusiness. According to the findings, the colonials benefited the most from the increased economic connectivity of the Anyer-Panarukan Road and faster delivery of goods such as sugar and coffee, while the indigenous population experienced poverty, hunger and socio-economic decline. This study encourages critical thinking about the economic impact of colonial initiatives by confirming that lavish infrastructure development often hides significant sacrifices from underprivileged communities.